Highly efficient visible-light-induced photocatalytic activity of Fe-doped TiO 2 nanoparticles - Paruchai Pongwan (2018)
Bare TiO 2 and nominal 5.0 at% Fe-doped TiO 2 nanoparticles were synthesized by the modified sol-gel method. The samples were physically characterized in order to obtain the correlation between structure and photocatalytic properties by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer, Emmett and Teller (BET), and UV-vis diffuse reflectance spectrophotometry (UV-vis DRS). XRD results indicated that phase structures of bare TiO 2 and Fe-doped TiO 2 nanoparticles were the mixture of anatase and rutile phases. The content of rutile phase in 5.0 at% Fe-doped TiO 2 nanoparticles decreased. TEM images revealed that the shape of bare and 5.0 at% Fe-doped TiO 2 was almost spherical and the average particle size was in the range of 10-30 nm. Specific surface areas of the samples were found as 75 and 134 m 2/g for bare TiO 2 and nominal 5.0 at% Fe-doped TiO 2, respectively. The results from UV-vis reflectance spectra clearly indicated the shift of absorption band edge towards visible region upon doping TiO 2 with iron. Photocatalytic activity of bare TiO 2 and 5.0 at% Fe-doped TiO 2 nanoparticles was examined by studying the mineralization of oxalic acid under visible light irradiation and the results clearly showed that Fe-doped TiO 2 sample exhibited higher activity than bare TiO 2.